2016
DOI: 10.1007/s10140-016-1380-7
|View full text |Cite
|
Sign up to set email alerts
|

CT imaging signs of surgically proven bowel trauma

Abstract: The objective of this study was to determine the incidence and interobserver agreement of individual CT findings as well as the bowel injury prediction score (BIPS) in surgically proven bowel injury after blunt abdominal trauma. This HIPAA-compliant retrospective study was IRB approved and consent was waived. All patients 14 years or older who sustained surgically proven bowel injury after blunt abdominal trauma between 1/1/2004 and 6/30/2015 were included. Admission trauma MDCT scans were independently interp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 22 publications
5
27
0
1
Order By: Relevance
“…Faget et al stated that these two findings were enough to confirm the presence of surgical intervention, with an OR of 128.9 (95% CI 9.5-999.9) and 140.5 (95% CI 9.3-999.9), respectively (8). Furthermore, in our study, interobserver agreement of these two findings was very good (k = 0.839 and 1.00, respectively), which is similar to a report done by LeBedis et al (20). Our study also manifested that two other MDCT findings that have significant correlation with surgical treatment were Janus signs and mesenteric stranding.…”
Section: Discussionsupporting
confidence: 91%
“…Faget et al stated that these two findings were enough to confirm the presence of surgical intervention, with an OR of 128.9 (95% CI 9.5-999.9) and 140.5 (95% CI 9.3-999.9), respectively (8). Furthermore, in our study, interobserver agreement of these two findings was very good (k = 0.839 and 1.00, respectively), which is similar to a report done by LeBedis et al (20). Our study also manifested that two other MDCT findings that have significant correlation with surgical treatment were Janus signs and mesenteric stranding.…”
Section: Discussionsupporting
confidence: 91%
“…In their cohort, 86.7% of patients with a bowel injury prediction score of 2 or 3 had a bowel injury at surgery (35). However, in the results of a subsequent study of a smaller cohort, LeBedis et al (36) found that only 56.3% of patients with surgically proven bowel injury had a bowel injury prediction score of 2 or 3. Further investigation into this model is warranted.…”
Section: Management Of Blunt Bowel and Mesenteric Injurymentioning
confidence: 94%
“…Patients with a BIPS ≥2 had a 19 times higher risk of sBBMI than patients with a lower score [23]. However, when applied to a retrospective series of 16 patients with surgically proven sBBMI [25], the BIPS was found to have a sensitivity of only…”
Section: Text Introductionmentioning
confidence: 91%